Cross-linking of T cell to B cell lymphoma by the T cell bispecific antibody CD20-TCB induces IFNγ/CXCL10-dependent peripheral T cell recruitment in humanized murine model - Cremasco, Floriana (PLoS One, 2021)
Diffuse large B cell lymphomas (DLBCL) are a highly heterogeneous subtype of Non Hodgkin Lymphoma (NHL), accounting for about 25% of NHL. Despite an increased progression-free survival upon therapy, 40–50% of patients develop relapse/refractory disease, therefore there remains an important medical need. T cell recruiting therapies, such as the CD20xCD3 T cell bi-specific antibody CD20-TCB (RG6026 or glofitamab), represent a novel approach to target all stages of DLBCL, especially those that fail to respond to multiple lines of treatment. We aimed for a better understanding of the molecular features related to the mode of action (MoA) of CD20-TCB in inducing Target/T cell synapse formation and human T cell recruitment to the tumor. To directly evaluate the correlation between synapse, cytokine production and anti-tumor efficacy using CD20-TCB, we developed an innovative preclinical human DLBCL in vivo model that allowed tracking in vivo human T cell dynamics by multiphoton intravital microscopy (MP-IVM). By ex vivo and in vivo approaches, we revealed that CD20-TCB is inducing strong and stable synapses between human T cell and tumor cells, which are dependent on the dose of CD20-TCB and on LFA-1 activity but not on FAS-L. Moreover, despite CD20-TCB being a large molecule (194.342 kDa), we observed that intra-tumor CD20-TCB-mediated human T cell-tumor cell synapses occur within 1 hour upon CD20-TCB administration. These tight interactions, observed for at least 72 hours post TCB administration, result in tumor cell cytotoxicity, resident T cell proliferation and peripheral blood T cell recruitment into tumor. By blocking the IFNγ-CXCL10 axis, the recruitment of peripheral T cells was abrogated, partially affecting the efficacy of CD20-TCB treatment which rely only on resident T cell proliferation. Altogether these data reveal that CD20-TCB’s anti-tumor activity relies on a triple effect: i) fast formation of stable T cell-tumor cell synapses which induce tumor cytotoxicity and cytokine production, ii) resident T cell proliferation and iii) recruitment of fresh peripheral T cells to the tumor core to allow a positive enhancement of the anti-tumor effect.